A biosensor based on chondroitin sulfate and DNA-peptide conjugate
By using chondroitin sulfate doped polyaniline composite material and DNA-polypeptide conjugates in biosensors, the problem of reduced sensitivity of existing biosensors in complex biological media is solved. , achieves the effect of rapid and sensitive detection of cortisol.
Patent Information
- Application Number
- CN202311060958.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-22
AI Technical Summary
Existing biosensors are prone to adsorbing nonspecific biomolecules in complex biological media, resulting in reduced sensitivity and making it difficult to detect cortisol quickly and accurately.
Using biosensors based on chondroitin sulfate doped polyaniline composite materials and DNA-polypeptide conjugates, electrodes with good conductivity and porous microstructure are constructed through technologies such as electrodeposition and peptide cross-linking to improve the sensitivity of cortisol detection .
It realizes rapid and sensitive detection of cortisol in complex biological media, with efficient anti-pollution effect and can directly detect cortisol in sweat, saliva and tears.
Smart Images

Figure CN117074497B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a biosensor based on a chondroitin sulfate-doped polyaniline composite material (CS / PANI) and a DNA-polypeptide conjugate. Background Art
[0002] Cortisol (CT) is primarily considered a stress hormone that plays a vital role in regulating blood pressure, immune system maintenance, fat digestion, and psychological health. The production and release of cortisol into the blood ensures the correct balance in the human body. The body responds to stress or danger by increasing glucose metabolism, controlling blood pressure, and reducing inflammation. Abnormal cortisol levels may have potential health effects. Excessively low cortisol in the body can cause fatigue, insomnia, vomiting, weight loss, and muscle weakness. Excessively high cortisol in the body can lead to Cushing's syndrome, severe fatigue, depression, cognitive difficulties, anxiety, cardiovascular disease, and obesity. Therefore, monitoring cortisol levels is important for prognostic and diagnostic purposes to reveal physiological and psychological states. Traditional laboratory techniques for quantitative cortisol detection include chromatography, radioimmunoassay, electrochemiluminescence immunoassay, and chemiluminescence. The disadvantages of these methods are that the detection process is cumbersome (it takes about 2 hours), the detection limit is high, and the detection selectivity for other structurally similar steroid hormones is poor.
[0003] Biosensors are a promising biomarker analysis product due to their advantages such as low cost, rapid response, easy miniaturization, and high sensitivity. Existing biosensors have high throughput capabilities and higher sensitivity, but these biosensors still have the following defects:
[0004] 1) Easy to adsorb complex biological media such as biomolecules;
[0005] 2) Nonspecific interactions occur at the sensing interface, resulting in a significant reduction in sensitivity.
[0006] Therefore, there is an urgent need to construct a biosensor with anti-fouling properties to suppress nonspecific adsorption for sensitive and rapid detection of biomarkers in complex biological media. Summary of the invention
[0007] To solve the above problems, the present invention provides a biosensor based on a chondroitin sulfate-doped polyaniline composite material and a DNA-polypeptide conjugate, which has good conductivity and a porous microstructure, provides a higher active area for biomolecule fixation, and thus improves the sensitivity of cortisol detection.
[0008] The present invention first provides a biosensor based on a chondroitin sulfate-doped polyaniline composite material and a DNA-polypeptide conjugate, wherein after polishing and cleaning the electrode, chondroitin sulfate (CS), aniline and hypochlorous acid are added to ultrapure water to form a mixed solution, and electrodeposition is performed on the electrode to obtain a GCE / CS / PANI electrode;
[0009] The polypeptides were then assembled onto the GCE / CS / PANI electrode to form a GCE / CS / PANI / Pep electrode. The electrode connected with the polypeptides was placed in a streptavidin solution, and finally the electrode was placed in a DNA solution for cross-linking to obtain a biosensor (GCE / CS / PANI / Pep / DNA).
[0010] The mixed solution, as a specific record of the embodiment, is composed of: 0.01g chondroitin sulfate, 0.241mL aniline and 2mL 2M perchloric acid, and 2.759mL ultrapure water is added to prepare 5mL of the mixed solution.
[0011] The electrodeposition was carried out at 0.1 mA cm -2 The deposition was carried out at a current density of .
[0012] The peptide is EKEKEKEPPPPC coupled with biotin, with a concentration of 2 mg mL -1 .
[0013] The DNA is a cortisol aptamer coupled with biotin.
[0014] The polypeptide is cross-linked to the electrode via a cross-linking agent; as a specific description of the embodiment, the cross-linking agent is SMCC solution.
[0015] The biosensor provided by the present invention is used to prepare products for detecting cortisol;
[0016] The present invention also provides a detection reagent for detecting cortisol, wherein the detection reagent contains the above-mentioned biosensor.
[0017] The biosensor prepared by the present invention can detect cortisol sensitively and rapidly in complex biological media. The dendritic DNA-polypeptide (Pep) conjugate is assembled through the specific interaction between biotin and streptavidin, achieving the effect of signal amplification. Combining the advantages of DNA-Pep and CS / PANI nanocomposite materials ensures that the biosensor plays a synergistic anti-pollution role and can directly detect cortisol in complex body fluids (sweat, saliva and tears). BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Figure 1 is the scanning electron micrograph of the nanocomposite modified electrode (AD), where A and B are the scanning electron micrographs of GCE / CS / PANI, and C and D are the scanning electron micrographs of GCE / CS / PANI / Pep / DNA. E and F are the EDS analysis spectra of GCE / CS / PANI / Pep / DNA, where a: C, b: N, c: O, d: P, and e: S in Figure E.
[0019] Figure 2 These are XPS spectrum images of nanocomposite modified electrodes, where Figure A is the spectrum image of GCE / CS / PANI, Figure B is the spectrum image of GCE / CS / PANI / Pep / DNA, Figure C is the contact angle of bare GCE, Figure D is the contact angle of GCE / CS / PANI, and Figure E is the contact angle of GCE / CS / PANI / Pep / DNA.
[0020] Figure 3 Fourier transform infrared spectra of CS / PANI (a) and CS / PANI / Pep / DNA (b).
[0021] Figure 4 These are curves of the four electrodes under cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and chronocoulometry (CC) methods, where A is the CV method, B is the EIS method, C and D are the CC method, and a is bare GCE, b is GCE / CS / PANI, c is GCE / CS / PANI / Pep, and d is GCE / CS / PANI / Pep / DNA.
[0022] Figure 5 Figure 5 is the non-specific adsorption resistance of three different sensors to different concentrations of single proteins, where A is Lys, B is BSA, C is Hg, and I: bare GCE, II: GCE / CS / PANI, III: GCE / CS / PANI / Pep / DNA. DF is the specific adsorption capacity of the two sensors in human body fluids (tears, saliva and sweat), where (A) is tears, (B) is saliva, (C) is sweat, and (I: bare GCE, III: GCE / CS / PANI / Pep / DNA / CT).
[0023] Figure 6 (A1-A3 and B1-B3) evaluated the attachment of FITC-BSA on bare GCE and GCE / CS / PANI / Pep / DNA; (A4 and B4) showed the mechanism of nonspecific adsorption on bare GCE and inhibition of nonspecific adsorption by GCE / CS / PANI / Pep / DNA.
[0024] Figure 7:The biosensor's detection effect on cortisol (A) is the DPV response diagram of GCE / CS / PANI / Pep / DNA before and after soaking in different concentrations of cortisol (a to g are concentrations of 0, 10 -12 , 10 -11 , 10 -10 , 10 -9 , 10 -8 and 10 -7 mol L -1 ); (B) is the dynamic response curve and linear calibration curve of the biosensor; (C) is the response of the biosensor to various substances (a: potassium chloride, b cortisol, c sodium chloride, d glacial acetic acid, e urea, f: sucrose, g ascorbic acid, h: citric acid monohydrate, i: D-fructose, j: glucose); (D) is the CV graph of GCE / CS / PANI / Pep / DNA after scanning 50 cycles in PBS with a pH of 7.4.
[0025] Figure 8 : DPV curves and corresponding response curves of the biosensor GCE / CS / PANI / Pep / DNA before and after incubation with different concentrations of sweat (A and B), tears (C and D), and saliva (E and F). DETAILED DESCRIPTION
[0026] The biosensor prepared by the present invention uses a chondroitin sulfate functionalized polyaniline nanocomposite as an electrode matrix. The nanocomposite has good conductivity and porous microstructure, provides a higher active area for biomolecule fixation, and improves the sensitivity of cortisol detection. At the same time, the polypeptide and the cortisol aptamer are fixed to the electrode, which can detect cortisol sensitively and highly selectively in complex media, and has a highly effective anti-pollution effect.
[0027] The abbreviations in the embodiments of the present invention are summarized as follows:
[0028] Glassy carbon electrode: GCE; polyaniline: PANI; polypeptide: Pep; chondroitin sulfate: CS; fluorescently labeled bovine serum albumin: FITC-BSA; lysozyme: Lys; bovine hemoglobin: Hg; cyclic voltammetry: CV; chronocoulometry: CC; electrochemical impedance spectroscopy: EIS; differential pulse voltammetry: DPV; chronopotentiometry: CP; Fourier transform infrared spectroscopy: FTIR; scanning electron microscopy: SEM.
[0029] The information of the reagents used in the examples of the present invention is shown in Table 1:
[0030] Table 1: Trial drug information table
[0031]
[0032]
[0033] The information of the instruments used in the embodiments of the present invention is shown in Table 2:
[0034] Table 2: Experimental instrument information
[0035] CHI660E Electrochemical Workstation Shanghai Chenhua Instrument Co., Ltd. KQ-300E Ultrasonic Cleaning Kunshan Ultrasonic Instrument Co., Ltd. Scanning electron microscopy Model of JSM-IT500 (Japan) Energy dispersive spectroscopy Model of JSM-IT500 (Japan) X-ray photoelectron spectroscopy Thermo-VG Sciences Fourier Transform Infrared Spectrometer Thermofisher / USA Optical contact angle measuring instrument Kruss Company of Germany
[0036] The present invention is described in detail below in conjunction with embodiments and drawings.
[0037] Example 1: Anti-fouling cortisol biosensor based on CS / PANI nanocomposites and DNA-peptide conjugates.
[0038] The biosensor prepared by the present invention is prepared by adding chondroitin sulfate, aniline and hypochlorous acid into ultrapure water after polishing and cleaning the electrode to form a mixed solution, one specific composition of which is as follows:
[0039] 0.01 g of chondroitin sulfate, 0.241 mL of aniline, and 2 mL of hypochlorous acid were added to 2.759 mL of ultrapure water to form 5 mL of a mixed solution.
[0040] The mixed solution was electroplated, and the obtained electrode was named GCE / CS / PANI electrode. The GCE / CS / PANI electrode was placed in SMCC solution for 1 hour at room temperature. Then, the sensor was immersed in peptide (biotin-EKEKEKEPPPPC) solution for 3 hours to allow the peptide to self-assemble on the modified electrode to form GCE / CS / PANI / Pep. After rinsing with ultrapure water, the GCE / CS / PANI / Pep was immersed in streptavidin solution. Finally, the modified electrode was placed in 10 -6 mol L -1 DNA solution (cortisol aptamer) was added to obtain the biosensor (GCE / CS / PANI / Pep / DNA).
[0041] The polishing described in the preparation method is performed by sprinkling 0.05 μm aluminum oxide powder on a polishing cloth, wetting it with distilled water, and using a counterclockwise circular method. The cleaning is performed by cleaning with a cleaning solution and then with deionized water.
[0042] The electrodeposition was carried out at 0.1 mA cm -1 The peptide solution was deposited for 3600 seconds using the chronopotentiometry (CP) technique at a current density of 2 mg mL -1 ; The streptavidin solution has a concentration of 2 mg mL -1 .
[0043] Example 2: Characterization of the surface morphology and microstructure of the biosensor (GCE / CS / PANI / Pep / DNA)
[0044] like Figure 1 As shown, both CS / PANI and CS / PANI / Pep / DNA nanocomposites exhibit nanostructures, and three-dimensional porous structures are formed between the interwoven nanowires. The difference between CS / PANI and CS / PANI / Pep / DNA nanocomposites is obvious. Some small protrusions and non-smooth rough interfaces can be observed on the surface of CS / PANI nanowires, while CS / PANI / Pep / DNA nanowires show very smooth interfaces. The interlaced nanowire structure of CS / PANI nanocomposites provides a larger surface area and more binding sites, and promotes the transport of electrons and ions for the immobilization of biomolecules.
[0045] Through EDS analysis of CS / PANI / Pep / DNA ( Figure 1 E and F) determined the chemical composition and confirmed the presence of C, N, O, P and S elements. The elemental composition (weight %) of CS / PANI / Pep / DNA was 76.81% (C), 15.41% (N), 7.30% (O), 0.07% (P) and 0.41% (S), respectively. There were no other additional peaks ( Figure 1 F) The purity of CS / PANI / Pep / DNA was confirmed.
[0046] Table 3: Element contents of CS / PANI and CS / PANI / Pep / DNA nanomaterials
[0047]
[0048] Figure 2 A shows that the peaks of C (C1s, 285 eV), N (N1s, 402 eV), O (O1s, 533 eV) and S (S2p, 208 eV) are clearly visible, which are the characteristic elements of chondroitin sulfate and polyaniline, proving that CS is successfully doped with PANI. Figure 2 As shown in Figure 3, after the immobilization of peptides, streptavidin and DNA, the peaks of C1s and N1s were greatly enhanced, and a new P2p peak (from DNA) appeared, indicating that these biomolecules have been immobilized on the CS / PANI interface. The quantitative XPS results show the atomic composition of CS / PANI and CS / PANI / Pep / DNA nanocomposites (Table 3). Compared with CS / PANI, the P2p and C1s contents of CS / PANI / Pep / DNA increased significantly, confirming the successful modification of these biomolecules on CS / PANI.
[0049] To evaluate the hydrophilicity of the surface, the contact angles of bare GCE, GCE / CS / PANI, and GCE / CS / PANI / Pep / DNA were measured. The contact angle of GCE / CS / PANI was 22.73° ( Figure 2 D), which is much smaller than the contact angle of bare GCE (59.72°, Figure 2 C), which is because the large number of hydrophilic groups such as carboxyl and hydroxyl groups from CS and amino groups from PANI lead to a decrease in the contact angle of GCE / CS / PANI. After the cortisol aptamer was immobilized, the contact angle of GCE / CS / PANI / Pep / DNA decreased to 13.78° ( Figure 2 E). These biomolecules (peptides, streptavidin, and DNA) immobilized on CS / PANI improve the hydrophilicity of the modified interface and enhance its anti-fouling properties. Therefore, the hydrophilicity of the biomolecules may be beneficial to the formation of a hydration layer and prevent the adsorption of nonspecific proteins.
[0050] FTIR spectra of CS / PANI and CS / PANI / Pep / DNA have been recorded ( Figure 3 ). FTIR analysis of CS / PANI (curve a) shows that at 626 cm -1 (CH), 1090cm -1 (COC), 1577cm -1 (NH) and 3447cm -1 Multiple peaks appeared at (OH), which were attributed to the specific groups of CS and PANI. More importantly, a new band appeared at 1273 cm in the FTIR spectrum of CS / PANI / Pep / DNA (curve b). -1 and 1381cm -1 (PO4 from DNA 3- ). This indicates that the cortisol aptamer has been successfully immobilized on the sensor surface and the biosensor has been successfully prepared.
[0051] from Figure 4 As can be seen from A, the electrochemical redox peak of bare GCE (curve a) is very small. The electrochemical redox peak of GCE / CS / PANI (curve b) is much larger than that of the bare glassy carbon electrode, because the CS-functionalized conductive polymer PANI nanowires have excellent conductivity. After the peptide is attached, the redox peak of GCE / CS / PANI / Pep (curve c) shows a large decrease, which is caused by the non-conductivity of the peptide. After assembling DNA on the modified electrode, the redox peak current of GCE / CS / PANI / Pep / DNA decreases again (curve d). This is due to the negatively charged DNA and the negatively charged probe [Fe(CN)6] 4- / 3- The electrostatic repulsion effect between them and the reason why DNA is not conductive.
[0052] EIS is an ultra-sensitive method for characterizing interfacial conductivity. The diameter of the semicircle in the figure is equal to the charge transfer resistance (Rct). Figure 4 As shown in Figure B, the Rct value of GCE / CS / PANI (curve b) is much smaller than that of bare GCE (528.6Ω, curve a), indicating that CS / PANI has the ability to significantly reduce impedance. With the sequential immobilization of peptides and DNA on CS / PANI, the Rct values of GCE / CS / PANI / Pep (962.3Ω, curve c) and GCE / CS / PANI / Pep / DNA (74464.1Ω, curve d) also increased significantly.
[0053] In addition, CC technology can observe very small changes in the electrochemically active surface area of the biosensor. According to the Cottrell equation, the active surface area of the modified electrode can be calculated. The effective areas of bare GCE, GCE / CS / PANI, GCE / CS / PANI / Pep, and GCE / CS / PANI / Pep / DNA are 0.046 cm -2 、0.865cm -2 、0.657cm -2 and 0.121cm -2 The effective area of GCE / CS / PANI is 18.8 times that of the bare electrode, indicating that the porous CS / PANI nanocomposite greatly enlarges the specific surface area. More importantly, the immobilization of peptides and DNA leads to a decrease in the electrochemical active area of the sensor. These results confirm the successful construction of the cortisol aptasensor, and the experimental results are consistent with the results of CV and EIS analysis.
[0054] Cottrell equation:
[0055]
[0056] Example 3: Anti-pollution effect of biosensor
[0057] The antifouling performance of different sensor surfaces was evaluated in single proteins (lysozyme (Lys), bovine serum albumin (BSA), and bovine hemoglobin (Hg)) and human body fluids (saliva, sweat, and tears). The peak current of DPV was tested to compare the changes in the sensor surface before and after incubation with single protein solutions and human body fluids for 30 minutes.
[0058] Before antifouling assessment, GCE / CS / PANI / Pep / DNA was incubated in cortisol solution (10 -6M) saturates the biosensor to ensure accurate biocontamination assessment. Signal suppression (%) is calculated as ΔI / I0×100%=(I0-I i ) / I0×100% (i=1,2,3,…). I0 represents the blank value, and I i Represents the detection value after incubation with the target solution.
[0059] The antifouling properties of different sensors were evaluated in single protein solutions (Lys, BSA, and Hg) and human body fluids (sweat, tears, and saliva). The antifouling properties of different modified electrodes were evaluated by comparing the signal suppression rates (ΔI / I0) of single protein solutions and human body fluids with different concentrations. The antifouling abilities of bare GCE, GCE / CS / PANI, and DNA-Pep conjugate modified biosensors to single protein solutions and human body fluids were recorded and compared. The results showed that the signal suppression rate of the bare glassy carbon electrode showed the maximum value, i.e., the nonspecific adsorption on the interface was the strongest. However, due to the synergistic antifouling effect of the DNA-Pep conjugate and CS / PANI nanocomposite, GCE / CS / PANI / Pep / DNA showed the smallest signal suppression rate and the strongest antifouling ability. Compared with the results of the laser confocal microscopy experiment, the adsorption of FTIC-BSA on the bare glassy carbon electrode was more serious, while the nonspecific adsorption of FTIC-BSA on GCE / CS / PANI / Pep / DNA was almost unobservable ( Figure 6 ).
[0060] Example 4: Biosensor Recognition Response to Cortisol
[0061] DPV measurement records the specific recognition reaction between cortisol in sweat, tears and saliva and the aptamer on the biosensor. The biosensor was immersed in sweat, tears and saliva of different concentrations (0.5%, 5%, 25%, 50%, 100%) for 30 minutes, and the DPV curves before and after incubation were recorded.
[0062] The specific capture of cortisol by the biosensor hinders the conversion of electrons to the sensor surface, resulting in a decrease in the DPV peak current. Figure 7 As shown in A, as the concentration of cortisol increases, the peak current becomes smaller and smaller until it is almost stable. As more and more target molecule cortisol is captured by the biosensor, the conductivity of the biosensor interface becomes weaker and weaker. The linear regression equation ( Figure 7 B) is ΔI / I0=-0.1635logC+0.00242(R2=0.999), with a range of 10 -12 -10 -7 mol L -1 , the detection limit (LOD) is as low as 0.333×10-12 mol L -1 .
[0063] Such excellent sensing performance is attributed to the 3D porous microstructure of CS / PANI nanowires (high surface area and excellent conductivity) and the advantages of DNA-Pep conjugates (strong antifouling ability and specific binding properties).
[0064] like Figure 7 C, by recording the -1 Target cortisol and several possible interfering substances (100 ng mL -1 ) to test the selectivity of the biosensor, including sodium chloride (Na + ), potassium chloride (K + ), urea, glacial acetic acid, sucrose, ascorbic acid, citric acid monohydrate, D-fructose, and glucose. The results showed that the signal suppression rate of these interfering substances on the sensor was much lower than that produced by cortisol even when the concentration was ten times higher than the detected target, indicating that the biosensor has excellent selectivity. The stability of the biosensor was verified by continuous cyclic voltammetry (CV). After running CV for 50 cycles, the peak current and potential of the biosensor did not change significantly ( Figure 7 D).
[0065] The analytical suitability of the biosensor for the detection of cortisol in sweat, tears, and saliva was evaluated using the DPV technique ( Figure 8 ). After measuring the cortisol content in sweat, tears, and saliva, the cortisol solution of accurate concentration was added to the test solution to detect the total cortisol content in the sample. The RSD of cortisol in the actual samples ranged from 2.94% to 4.23%; the recovery rate ranged from 98% to 103.6% (Table 4).
[0066] Table 4: Data table of cortisol levels in sweat, tear and saliva samples measured using biosensors
[0067]
[0068]
[0069] In summary, the present invention constructs an anti-pollution biosensor for detecting cortisol in complex liquids (sweat, tears and saliva) based on chondroitin sulfate (CS) functionalized conductive polymer polyaniline (PANI) and DNA-Pep conjugates. Both chondroitin sulfate and DNA-Pep conjugates can be used as anti-pollution nanomaterials to ensure that the biosensor has excellent anti-pollution capabilities in single protein solutions and complex human body fluids. CS / PANI nanocomposites have good conductivity and porous microstructures, providing a high active area for biomolecule fixation, thereby improving the sensitivity of cortisol detection. More importantly, since DNA-Pep conjugates can be simply designed into different functional peptides and different aptamers, this strategy is expected to construct a variety of anti-pollution biosensors for rapid detection of other disease biomarkers in clinical diagnosis.
Claims
1. A biosensor, characterized in that: The biosensor is obtained by adding chondroitin sulfate, aniline and perchloric acid to ultrapure water to form a mixed solution after polishing and cleaning the electrode, and performing electrodeposition on the electrode; then assembling the polypeptide on the electrode, placing the electrode connected with the polypeptide in a streptavidin solution, and finally placing the electrode in a DNA solution for cross-linking to obtain the biosensor; the composition of the mixed solution is as follows: 0.01g chondroitin sulfate, 0.241mL aniline and 2mL perchloric acid with a concentration of 2M, and 2.759mL ultrapure water is added to prepare 5mL of the mixed solution; the sequence of the polypeptide is EKEKEKEPPPPC, and it is coupled with biotin; the DNA is a cortisol aptamer coupled with biotin.
2. The biosensor according to claim 1, wherein The electrodeposition is carried out at 0.1 mA cm -2 The deposition was carried out at a current density of .
3. Use of the biosensor according to claim 1 in preparing a product for detecting cortisol.
4. The use according to claim 3, characterized in that The product is a detection kit.
5. A product for detecting cortisol, characterized in that: The product comprises the biosensor according to claim 1.
6. A method for detecting cortisol in body fluids, characterized in that: The method is to use the biosensor described in claim 1 for detection.
Citation Information
Patent Citations
Preparation method of self-adhesive conducive hydrogel used as electrode
CN109762210A
Nanoelectrode biosensor based on nucleic acid aptamer and application of nanoelectrode biosensor
CN114199969A